Rake. Series 4 [videorecording (DVD)] - Roxburgh, Richard; Day, Matt, 1971-; Dykstra, Russell (Acorn Media, 2017)
Smart but self-destructive lawyer Cleaver Greene faces new challenges to his career and his personal life as the hit Australian comedy drama returns. Last seen dangling from a runway hot air balloon, Cleaver crashes into the window of wanted criminal Edgar Thompson. Forced out of hiding, Edgar stirs up a huge corruption scandal involving most of the politicians in Sydney, and vows revenge on Cleaver.